A formalized transition program for cystic fibrosis: A 10‐year retrospective analysis of 97 patients in Lyon. Issue 7 (23rd March 2021) - Bourgeois, Gaelle; Magne, Fanny; Nove Josserand, Raphaele; Durupt, Stephane; Durieu, Isabelle; Reix, Philippe; Reynaud, Quitterie
Abstract: Introduction: The prognosis of people diagnosed with cystic fibrosis (CF) has dramatically improved over the past decade in France, largely due to advances in CF care management, including an emphasis on chronic maintenance medications. Currently, the majority of French CF patients are adults, which means that they went through a transition process from receiving care at a pediatric CF center to receiving care at an adult CF center. To determine the impact of the transfer on clinical evolution, we report the transition procedure of our CF center in Lyon. Materials and Methods: From January 2006 to December 2016, 97 CF patients underwent a standardized process of transitioning from the pediatric to the adult CF center in Lyon. We compared the clinical evolution of these patients during three periods, starting the year before transition and ending the year after transition. Clinical data taken into account were forced expiratory volume in 1 s (FEV1 in liters), body mass index (BMI in kg/m 2 ), pulmonary colonization, number of antibiotic courses, number of days of hospitalization per year, and outpatient visits per year. Results: No significant differences were observed between respiratory and nutritional status, respiratory microbiome, number of antibiotic courses, or number of hospitalizations or visits when comparing the threeperiods of observation around transition (the year before, the first year after, and the second year after transfer). Conclusion: The standardized transition procedure used in Lyon is associated with the clinical stability of our CF patients.